KETERAMPILAN MENULIS TEKS CERPEN MENGGUNAKAN TEKNIK COPY THE MASTER DAN TEKNIK MIND MAPPING SISWA KELAS XI SMA NEGERI 2 PADANG PANJANG - Safitri, Ramadani; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2019)
ABSTRACTÂ This study aims to describe students short story writing skills using the master copy technique and mind mapping techniques. This type of research is quantitative with analytical descriptive method. Research sampling is done by purposive sampling technique. The instrument used to collect data in this study is the performance test, which is writing short story texts. The research data ini the form of short story writing skills using the master copy technique and mind mapping technique. The research data collection technique is by analyzing students short story writing skills by apllying the master copy technique and mind mapping technique. Indicators used to assess short story writing skills, namely structure, instrinsic elements, and linguistic elements.Â Based on the result of the study, it can be concluded that. First, short story writing skills using the master copy the technique of the eleventh grade students of Padang Panjang public high school 2 are in good qualification because the average value of short story text writing skills using the master copy technique is 82.07. Second, short story writing skills using mind mapping techniques of the eleventh grade students of Padang Panjang 2 high school are in excellent qualifications because the average value of short story writing skills using mind mapping technique is 88.26. Third, based on the calculated average values for the two texts, there is a significant different between the short story writing skills using the master copy technique of the eleventh grade students of Padang Panjang 2 high school.Kata kunciÂ : keterampilan menulis, teks cerpen, copy the master, mind mapping